The Effects of Macroeconomic Business Cycle on Earnings Management: Evidence from Korean Companies (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper examines the relationship between macroeconomic business cycles and earnings management, specifically, whether firms make more earnings management during the boom period of the macroeconomic business cycle or during contraction period of the business cycle. Earnings management is activities of getting certain benefits by involving in external financial reporting or confusing certain stakeholders through adjustments to accruals without involvement of cash flows or with cash flows through real activities. In examining the relationship, we used the models of Kothari et al. (2005) and Cohen et al. (2008) for accrual-based earnings management (AEM) and real activities earnings management (REM), respectively, for earnings management proxies. We also used composite economic indicators, real GDP growth and BSI for proxies of macroeconomic business cycles. Using a data set for Korean companies listed from 2005 to 2017, we developed and tested a panel regression model with fixed effects to capture the relationship. The results show that companies perform earnings management more often during economic booms than during contraction periods. This is interpreted that firms try to avoid disclosure of lower net income compared to the expectations of analysts or average net income of companies in the same industry. This study is giving insights to external auditors when they perform external audit on the firms’ financial statement, they need to spend more attention on the firms’ earning management behaviors during boom period rather than contract period. It applies the same to analysts of securities.